First record of the invasive bee Anthidium manicatum (Hymenoptera: Megachilidae) in Chile - Montalva, Jose Miguel; Ríos, Mauro; Vivallo, Felipe (Journal of Melittology, 2015)
The Palearctic wool carder bee Anthidium manicatum (Linnaeus) is recorded for the first time in Chile based on eight specimens collected on Lavandula sp. (Lamiaceae) in San Bernardo, Metropolitan Region. This new record expands the invasive range of this species in South America, confirming previous predictions based on an ecological niche model.